2015
DOI: 10.1371/journal.pone.0124059
|View full text |Cite
|
Sign up to set email alerts
|

Upregulation of Programmed Death-1 and Its Ligand in Cardiac Injury Models: Interaction with GADD153

Abstract: PurposeProgrammed Death-1 (PD-1) and its ligand, PD-L1, are regulators of immune/ inflammatory mechanisms. We explored the potential involvement of PD-1/PD-L1 pathway in the inflammatory response and tissue damage in cardiac injury models.Experimental DesignIschemic-reperfused and cryoinjured hearts were processed for flow cytometry and immunohistochemical studies for determination of cardiac PD-1 and PD-L1 in the context of assessment of the growth arrest- and DNA damage-inducible protein 153 (GADD153) which … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
63
1
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(68 citation statements)
references
References 35 publications
2
63
1
2
Order By: Relevance
“…Acute coronary syndrome in BALB/c mice increased the percentage of heart cells expressing PD‐1+ and PD‐L1+. These experiments confirmed that PD‐1/PD‐L1 play an important role in reducing T‐cell‐mediated autoimmune myocarditis 35 …”
Section: Cardiotoxicity Caused By Checkpoint Inhibitors Treatmentsupporting
confidence: 62%
See 1 more Smart Citation
“…Acute coronary syndrome in BALB/c mice increased the percentage of heart cells expressing PD‐1+ and PD‐L1+. These experiments confirmed that PD‐1/PD‐L1 play an important role in reducing T‐cell‐mediated autoimmune myocarditis 35 …”
Section: Cardiotoxicity Caused By Checkpoint Inhibitors Treatmentsupporting
confidence: 62%
“…The expression of GADD153 in proliferating cells is very low, but it is strongly induced by cellular stresses, such as glucose deprivation, genotoxic agents, and other growth‐arresting factors. Knockdown of GADD153 confers cardioprotective effect in mice model 35 . PD‐1/PD‐L1 pathway activation leads to inhibition of the prosurvival signaling in T cells like PI3K/Akt pathway, which is an important kinase pathway after reperfusion injury.…”
Section: Cardiotoxicity Caused By Checkpoint Inhibitors Treatmentmentioning
confidence: 99%
“…Fibrinogen‐like protein 2 (FGL2), a member of the fibrinogen family, is expressed either as a pro‐coagulative membrane protein or as an immunosuppressive secreted protein . FGL2 over‐expression resulted in deterioration of heart function in rats with acute EAM, increased the inflammatory cell infiltrations, and increased the level of brain natriuretic peptide (BNP), tumour necrosis factor‐ α , interleukin‐6 (IL‐6) and IL‐17 Increased expression of PD‐1/PD‐L1 in ischaemia re‐perfused and cryoinjured hearts was associated with a marked increase in IL‐17 . In our current study we explored the involvement of the PD‐1/PD‐L1 pathway in immunotolerance as a potential mechanism for the pathogenesis of EAM mediated by FGL2.…”
Section: Introductionmentioning
confidence: 99%
“…These mice experience increased influx of monocytes, CD4 T cells, and CD8 T cells in association with increased TNFα. However, the role of PD-1 ligation in human atherosclerosis remains uncertain 383940 . It is against this background that we find phenotypically naive CD8 T cells from ACS patients have a reduced capacity for IL-2 production, and this correlates with increased expression of PD-1.…”
Section: Discussionmentioning
confidence: 99%